Role of Indium Alloying with Lead as a Means to Reduce the Passivation Phenomena in Lead/Acid Batteries - Abdel-Rahman El-Sayed; Hossnia S. Mohran; Hoda Abdel Shafy Shilkamy (International Journal of Electrochemistry)
The influence of indium content on the anodic behaviour of Pb-In alloys in 4 M H2SO4 solution is investigated by potentiodynamic, potentiostatic, chronopotentiometric, and cyclic voltammetric techniques. The composition and microstructure of the corrosion layer on Pb-In alloys are characterized by X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy analysis (EDX), and scanning electron microscopy (SEM). The potentiodynamic and chronopotentiometric curves show that the anodic behavior of all investigated electrodes exhibits active/passive transition. The active dissolution (except for alloy I) and passive currents increase with increasing both In content and temperature. This indicates that the conductivity of the anodic film on Pb-In alloy is enhanced. This study exhibits that indium catalyses the oxidation of Pb (II) to Pb (IV) and facilitates the formation of a more highly conductive corrosion layer on lead. Alloy I (0.5% In) exhibits that the corrosion rate is lower, while the passive current is higher than that of Pb. XRD, EDX, and SEM results reveal that the formation of both PbSO4 and PbO on the surface decreases gradually with increasing In level in the alloy and completely disappear at higher In content (15% In). Therefore, recharge of the battery will be improved due to indium addition to Pb.